Investigation of exercise addiction and mental toughness levels of sports science faculty students - Göktaş, Zekeriya; Güzel, Melis Ceyda (Journal of Dependence, 2023)
Objective: The study aimed at searching for levels of exercise addiction and mental thoughness of the students who studied at the sports sciences faculty in terms of different variables and determining the correlation between levels of exercise addiction and mental resilience. Method: 390 students (193 male students and 197 female students) who studied at the sports sciences faculty of Balıkesir University during 2020-2021 academic year joined the study. As data collection tools, “Demographic Information Form”, “Exercise Addiction Scale” and “Sports Mental Toughness Questionnaire” were used. Results: A significant difference was found between participants’ level of exercise addiction and variables of age and exercise frequency. When level of mental thoughness was studied, it was identified that there was a significant difference in terms of variables of age and exercise frequency. The correlation between levels of exercise addiction and mental resilience was investigated and a positive and low level of significant correlation was found. Conclusion: The participants’ level of exercise addiction was in the risky group while their level of mental thoughness was above the moderate level. Male university students had higher mental thoughness as compared to female students in terms of gender variable. As participants’ ages increased, so did their mental thoughness level but their addiction risk level decreased. Besides, as participants’ number of exercises per week increased so did their addiction level and mental thoughness level.